Association of СОМТ gene polymorphisms with Parkinson’s disease - Svetlana A. Ivanova; Valentina M. Alifirova; Irina A. Zhukova; Vladimir V. Tiguntsev; Ivan V. Pozhidaev; Diana Z. Osmanova; Olga Yu. Fedorenko; Maxim B. Freydin; Yulia S. Mironova; Natalia G. Zhukova; Nikolay A. Bokhan; Anton J.M. Loonen (Бюллетень сибирской медицины)
Parkinson’s disease (PD) is one of the most serious and widespread neurodegenerative disorders. Genetic susceptibility plays a significant role in the development of PD.The aim of our study was to investigate associations between single nucleotide polymorphisms (SNPs) of the COMT gene coding dopamine catabolism enzyme and Parkinson’s disease.Materials and methods. In this study seven SNPs (rs4680, rs6269, rs4633, rs4818, rs769224, rs165774, rs174696) of COMT were genotyped. 232 patients with PD and 127 healthy individuals in the Siberian region of Russia were examined. Venous blood samples were drawn as a marker of PD. Statistical differences in the prevalence of alleles and genotypes between groups of patients were assessed using IBM SPSS Statistics 23.1 software.Results. A significant association between the rs165774 polymorphism and PD was observed. Our study demonstrates that polymorphisms in the COMT gene may play an important role in the pathophysiology of Parkinson’s disease.